Web wars: males of the golden orb-web spider invest more in fights for mated females. (25th March 2021) - da Silva, Amanda Vieira; Oliveira, Reisla; Peixoto, Paulo Enrique Cardoso
Abstract: In addition to resource value, the cost of finding mates may affect how much males invest in fights for females. The cost of finding females may be imposed through natural factors extrinsic to males, such as female spatial distribution and predation pressure, which can be challenging to simulate in laboratory conditions. Therefore, studies under natural conditions may be suitable for understanding how the costs of finding mating partners affect male investment in fights. We used the spider Trichonephila clavipes to evaluate the hypotheses that males in field conditions invest more in contests for access to 1) unmated and 2) more fecund females and 3) when access to females is harder. To test these hypotheses, we recorded the occurrence, duration, and escalation of induced contests between males located in webs of females that differed in reproductive status (estimated by female life stage), fecundity (estimated by female abdominal area), and spatial distribution (i.e., isolated or aggregated with webs of other females). The occurrence and duration of contests were unrelated to female value or search costs. However, the probability for escalation was higher when males were fighting for adult (and probably mated) females. We also found that males tended to start a contest more often in aggregated webs. These results indicate that males of T. clavipes adjust investment in contests but contrarily to what we expected. We suggest that males invest more in contests for adult females because they are defending females that they previously fertilized to avoid sperm competition. Abstract : When should a male fight for a mate? We investigated how males of the golden silk orb-web spider adjust their fight intensity for mates in response to female quality, and the costs they pay to access them. We found that males adopt more aggressive behaviors against rivals when fighting for mated females independent of the costs to search for partners. They also exhibited a tendency to fight more often when located in aggregated webs of females. These results have important implications to better understand the evolution of male fighting behaviors.